Costumes and Mourning Rituals in Widowhood Practices as Grief Management Strategies Mitigating Mortality Salience in Ondo Kingdom Nigeria - Badeji , Susan Olubukola; Akpunne, Bede Chinonye; Ajetunmobi , Oluwasegun (Corpus Intellectual, 2024)
This study explored the role of costumes and mourning rituals in widowhood practices in Nigeria, and how these practices serve as strategies for grief management mitigating mortality salience (MS). The terror management theory (TMT) was used to explain the application of both proximal and distal defenses to mitigate the anxiety of death caused by the demise of a relation. Mourning rituals and widowhood practices among the Ondo people of southwestern Nigeria among others include a proper announcement of the death of the husband, sleeping and sitting on the bare floor for seven days, mandatory spiritual bath as a form of cleansing and washing off the connections with spirit of the dead and subsequent adornment with facial makeup and bright costumes and use of incense to bid a deceased husband farewell are cultural strategies of the terror management theory. In mitigating the motility salience, mourning rituals help bereaved individuals acknowledge the reality of the death, embrace the pain of the loss, offer the opportunity for a remembrance of the deceased and shift the relationship shared with the deceased from physical to memory. Also, these rituals help bereaved people develop of new self-identity, provide an avenue to search for meaning in life and death, and serve as a means to receive social support.